Síntese de catalisadores baseados em silicatos mesoporosos contendo ferro ou nióbio para uso em sistemas catalíticos heterogêneos - Jakelyne Viana Coelho (2013)
This thesis deals with the development of new materials based on mesoporous silicate, modified with iron and niobium atoms, for use in catalytic processes. The focus of this work was to develop mesoporous materials with high specific area, that act as a catalyst in the oxidation and isomerization, to obtain fine chemicals and in the oxidation/degradation of molecules model, simulating textile dyes an industrial waste. The synthesis of these materials was performed by polymerizing tetraethoxysilane (TEOS) as silica source, supramolecular arrengements of cetyltrimethylammonium bromide (CTAB) as structure drivers, with iron and niobium salts. The materials were characterized by various characterization techniques, and the Mossbauer spectroscopy and XRD indicated the incorporation of Fe and Nb in the silicate structure. Studies textural point materials with high surface area, with values of 1165 and 799 m2 g-1 for Fe3+-MCM and Fe2+-MCM, respectively, and 960 to 910 m2g-1 to Nb-MCM and Nb-MCM//H2O2 respectively. The reactions involving the oxidation of -pinene using niobium catalysts showed that the presence of niobium assisted the conversion of -pinene into oxidized products of high added value. It was possible to observe the oxidation/degradation of Rhodamine-B molecule using ESI-MS analysis and the same catalyst. For the isomerization of -pinene catalysts modified with iron atoms were used. It was possible to observe a greater conversion of -pinene into value added products, highlighting the higher catalytic efficiency of the modified materials with iron when compared with MCM-41. The reactions of oxidation/degradation of methylene blue model molecule were performed, also using the modified catalysts with iron, and monitored by ESI-MS. It was observed that the iron-containing materials are able to generate oxygen radicals, which react with the methylene blue molecule (conversion of about 90%). In conclusion this study aimed to cooperate, in a general way, for the understanding of the effects of metal ions in the structure of mesoporous silicates, such as MCM-41, as well as improve to potential interest of these materials for the industry.